2013
DOI: 10.1124/dmd.113.054486
|View full text |Cite
|
Sign up to set email alerts
|

Disposition and Metabolism of Darapladib, a Lipoprotein-Associated Phospholipase A2 Inhibitor, in Humans

Abstract: The absorption, metabolism, and excretion of darapladib, a novel inhibitor of lipoprotein-associated phospholipase A 2 , was investigated in healthy male subjects using [14 C]-radiolabeled material in a bespoke study design. Disposition of darapladib was compared following single i.v. and both single and repeated oral administrations. The anticipated presence of low circulating concentrations of drug-related material required the use of accelerator mass spectrometry as a sensitive radiodetector. Blood, urine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…This study evaluated the effects of severe renal impairment, compared with normal renal function, on the pharmacokinetics and safety/tolerability of oral repeat dosing of darapladib. Although a human radiolabel study had previously shown that less than 0.5% of the administered darapladib dose is eliminated by the renal route , severe renal impairment resulted in considerable reduction in darapladib overall clearance in total and unbound darapladib as well as in all three metabolites. Exposure increase was most pronounced in unbound darapladib exposure which is the entity presumably responsible for the pharmacological and toxicological actions of darapladib.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This study evaluated the effects of severe renal impairment, compared with normal renal function, on the pharmacokinetics and safety/tolerability of oral repeat dosing of darapladib. Although a human radiolabel study had previously shown that less than 0.5% of the administered darapladib dose is eliminated by the renal route , severe renal impairment resulted in considerable reduction in darapladib overall clearance in total and unbound darapladib as well as in all three metabolites. Exposure increase was most pronounced in unbound darapladib exposure which is the entity presumably responsible for the pharmacological and toxicological actions of darapladib.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to CYP3A, darapladib is also a substrate for P‐glycoprotein . Studies have shown conflicting effects of uraemia on P‐glycoprotein activity in the intestine, kidney and liver .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to gain an insight into the possible mechanisms behind this disparity, the relative disposition and metabolism of radiolabelled drug was compared at steady‐state and after single oral and i.v. doses of 14 C‐drug . The design of the steady‐state arm of the study was such that a single radiolabelled dose was administered on day 11 during the 14 day repeat oral dosing of non‐labelled drug.…”
Section: Special Considerationsmentioning
confidence: 99%
“…According to the biopharmaceutical classification system (BCS), darapladib is considered to be a Class 4 substance due to its low passive permeability (≤7 nm/s at pH 5.5) and low solubility (>1, 0.8, 0.3 and <0.1 mg/mL at pH 2, 4, 6 and 8, respectively) [Unpublished data]. Consistent with Class 4 BCS products, the absolute bioavailability of oral darapladib is low (4% for darapladib enteric coated tablet [Unpublished data] and 12% for a solution [ 6 ]). Compared with the fasted state, administration of a high fat meal with darapladib enteric coated tablet resulted in a 19% increase in systemic exposure (AUC) to darapladib and the higher exposure is not considered to be clinically relevant [Unpublished data].…”
Section: Introductionmentioning
confidence: 99%